A comprehensive assessment of arterial signal coordination through a case study - Peter Horbachov; Yevhen Liubyi; Stanislav Svichynskyi; Dmitriy Muzylyov; Vitalii Ivanov (Transportation Research Interdisciplinary Perspectives)
Many municipalities in developing countries still face the problem of choosing the most effective way to advance their traffic control systems based on isolated fixed-time traffic signals. The major alternatives are transitioning to adaptive traffic signals or coordinating existing isolated ones. To demonstrate the potential of coordination, the effectiveness of the coordinated timing plan for six local signalized intersections on the 1.8-kilometer-long segment of Nauky Ave. (arterial) in Kharkiv, Ukraine, has been thoroughly evaluated. For this purpose, the travel time along the coordinated segment was sampled. Also, the average travel time and vehicle speed on the minor street approaches to the coordinated intersections were calculated based on TomTom data. As a result, the coordinated timing plan clearly showed its high effectiveness. Considering the low implementation costs, this testifies that in cities where most traffic signals are isolated and fixed-time, the coordination may be much preferable to installing expensive adaptive signals. The obtained results confirm that coordination can serve as an effective traffic management measure to ensure sustainable traffic in municipalities with limited budgets. The main research benefit is obtaining a comprehensive practical assessment of the effectiveness of the implemented traffic control measures on a 1.8 km section of the arterial.